Green Supply Chain Management and Sustainability Performance: The Mediating Role of Sustainable Competitive Advantage - I Wayan Santika; Komang Agus Satria Pramudana; I Wayan Gede Sedana Yoga; Fridayana Yudiaatmaja; Bagas Dwi Arissaputra Bachtiar (Jurnal Ilmiah Akuntansi, 2026)
This study examines the relationship between green supply chain management and sustainability performance and investigates the mediating role of sustainable competitive advantage. The study focuses on employees of electronic distribution companies in Bali, Indonesia. Data were collected through questionnaires from 70 respondents and analyzed using partial least squares structural equation modeling. The results show that green supply chain management is positively associated with both sustainable competitive advantage and sustainability performance. Sustainable competitive advantage is also positively associated with sustainability performance and partially mediates the relationship between green supply chain management and sustainability performance. These findings indicate that green supply chain practices generate stronger sustainability outcomes when firms transform environmental initiatives into strategic capabilities that improve operational efficiency, market differentiation, and stakeholder trust. The study contributes to the sustainability accounting and supply chain literature by clarifying the mechanism through which environmental practices are translated into economic, environmental, and social performance. It also highlights the importance of integrating green supply chain practices with competitive strategy and sustainability-oriented performance measurement.